Temperature-dependent phonon dynamics of supported and suspended monolayer tungsten diselenide - Carvalho, Thais C. V.; Araujo, Francisco D. V.; dos Santos, Clenilton Costa; Alencar, Luciana M. R.; Ribeiro-Soares, Jenaina; Late, Dattatray J.; Lobo, Anderson Oliveira; Souza Filho, Antonio Gomes; Alencar, Rafael S.; Viana, Bartolomeu C. (AIP Advances, 2019)
Two-dimensional materials exhibit great potential for high-performance electronics applications and the knowledge of their thermal properties is extremely necessary, since they are closely related to efficient heat dissipation and electron-phonon interactions. In this study we report the temperature-dependence of the out-of-plane A(1g) Raman mode of suspended and supported CVD-grown single-crystalline tungsten diselenide (WSe2) monolayer. The A(1g) phonon wavenumber is linearly red-shifted for temperature ranging from 98 to 513 K, with first-order temperature coefficients beta of -0.0044 and -0.0064 cm(-1)/K for suspended and supported monolayer WSe2, respectively. The higher beta module value for supported sample is attributed to the increase of the phonon anharmonicity due to the phonon scattering with the surface roughness of the substrate. Our analysis of the temperature-dependent phonon dynamics reveal the influence of the substrate on thermal properties of monolayer WSe2 and provide fundamental information for developing of atomically-thin 2D materials devices. (C) 2019 Author(s).